Two new damselflies from the Eocene Green River Formation (Odonata, Zygoptera, Dysagrionidae, Thaumatoneuridae) - Nel, André (Zootaxa, 2024)
Two new damselflies are described on the basis of isolated wings from the Eocene Green River Formation (Colorado, USA), the eodysagrionine new genus and species Gusagrion coloratum and the dysagrionid new species Petrolestes inexpectatus. These new taxa confirm the great diversity of the fauna of large damselflies in this formation, currently much more important than the smaller damselflies of Lestoidea and Coenagrionoidea clades and of the large Anisoptera. It seems that important changes occurred in the faunal composition of the Odonata between the Eocene and Oligocene.